2021
DOI: 10.3390/ijerph182211871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mindfulness-Based Stress Reduction (MBSR) on Stress, Heart Rate Variability, Affect, and Wellbeing among People with Schizophrenia

Abstract: Mindfulness-based stress reduction programs have been found to be effective in reducing the stress response and improving the psychological wellbeing of various populations. We aimed to confirm the effects of a mindfulness-based stress reduction program on perceived stress, heart rate variability, positive and negative affect, and subjective wellbeing of community-dwelling people with schizophrenia. The participants in this study were 26 people with schizophrenia (experimental group: 14, control group: 12) enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…Findings from the current study reveal the impact of this variability: on average, spikes in PTSD symptoms degraded autonomic function, at least temporarily. If one conceptualized PTSD symptoms as a stressor in and of itself, then findings from this study merge with a body of literature showing how stress affects HRV (49) and how certain interventions (e.g., slow breathing, yoga, mindfulness-based stress reduction) may mitigate that impact (50,51).…”
Section: Discussionsupporting
confidence: 54%
“…Findings from the current study reveal the impact of this variability: on average, spikes in PTSD symptoms degraded autonomic function, at least temporarily. If one conceptualized PTSD symptoms as a stressor in and of itself, then findings from this study merge with a body of literature showing how stress affects HRV (49) and how certain interventions (e.g., slow breathing, yoga, mindfulness-based stress reduction) may mitigate that impact (50,51).…”
Section: Discussionsupporting
confidence: 54%
“…As a result, patients' health outcomes would be significantly improved. As an example, studies have suggested that the MBSR program greatly decreased patients' symptom burden (physical wellbeing) and improved patients' psychological wellbeing and QoL (Zimmaro et al, 2020 ; Kim et al, 2021 ). Moreover, empirical studies suggested that the MBSR program also improved patients' treatment adherence and then enhanced the anticancer treatment effects, as well as improved physical status, psychological wellbeing, and QoL (Cillessen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study observed significantly increased SDNN and HF within a group of patients with nonmetastatic breast cancer receiving 4 weeks of MBSR intervention [ 32 ]. From a medical perspective, SDNN indicates stress and mortality [ 33 ]; lower SDNN values indicate that an individual’s ability to adapt to stress is low and that their degree of stress is high [ 34 ]. Decreased values of RMSDD and HF values are also associated with higher morbidity and mortality risk [ 35 ].…”
Section: Discussionmentioning
confidence: 99%